The Influence of Promotion, Information Quality, and Price Perception on Impulsive Buying on the Shopee Live Feature Among Students of UPN "Veteran" East Java - Michael Daniel Pinontoan; Ugy Soebiantoro (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
After the emergence and develops of e-commerce in Indonesia, consumer behavior began to shift, whereas now consumers no longer had to come to a store or a mall to go shopping and see the value of a product. They could just simply visit the targeted website or e-commerce platform, which is Shopee in this case. Shopee has provided many ways and selling features inside their platform for business owners to be able to interact directly with their product/service buyers even though they are not in the same physical environment. Among them is live streaming marketing via the Shopee live feature. This feature is pretty familiar to Shopee consumers or users, especially among UPN "Veteran" East Java students. The purpose of this study is to analyze the effect of promotions, information quality, and price perceptions on impulse buying via the Shopee Live feature on UPN "Veteran" East Java students. This study uses quantitative methods which are processed using the SmartPLS 4 program, with a sample size of 100 respondents. The results showed that promotions, information quality, and price perceptions have a positive and significant effect on impulse buying.